Emojis in Digital Governance: Empirical Insights from Indonesian Ministries - Kusumasari, Bevaola; Dwi Santoso, Anang; Sajida, Sajida (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
This study explores how Indonesian ministries create impressions to the public through their use of emojis on X (previously Twitter ). Based on a qualitative content analysis of 1,897 tweets, this research finds evidence of the strategic use of emojis in ingratiation, self-promotion, exemplification, and supplication. The findings indicate that emojis are not only used to raise public engagement, but also to create an image of positivity and friendliness. Ingratiation and self-promotion emerged as the most salient strategies. This paper examines the role of emojis in government communication and contributes to the understanding of digital political communication with further practical insights into managing public relations for government agencies.